2016
DOI: 10.1007/s13361-016-1530-x
|View full text |Cite
|
Sign up to set email alerts
|

Cationized Carbohydrate Gas-Phase Fragmentation Chemistry

Abstract: We investigate the fragmentation chemistry of cationized carbohydrates using a combination of tandem mass spectrometry, regioselective labeling, and computational methods. Our model system is D-lactose. Barriers to the fundamental glyosidic bond cleavage reactions, neutral loss pathways, and structurally informative cross-ring cleavages are investigated. The most energetically favorable conformations of cationized D-lactose were found to be similar. In agreement with the literature, larger group I cations resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
82
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 63 publications
4
82
0
Order By: Relevance
“…A CID study of fragmentation of d ‐lactose with H 0 , Li + , and Na + reported similar observations. The larger cations required higher collision energies to dissociate the d ‐lactose . Larger cations were thought to have higher fragmentation energies because they have more coordinated oxygen atoms.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A CID study of fragmentation of d ‐lactose with H 0 , Li + , and Na + reported similar observations. The larger cations required higher collision energies to dissociate the d ‐lactose . Larger cations were thought to have higher fragmentation energies because they have more coordinated oxygen atoms.…”
Section: Resultssupporting
confidence: 92%
“…The size of cation additive and degree of sucrose fragmentation were found to be inversely related, so fewer sucrose ions fragmented when larger cation additives were used. It has been reported that higher collision energies are required to dissociate carbohydrates combined with larger cations, because these cations have more coordinated oxygen atoms . Our observations agree with the previous results, showing that heavier cations cleave fewer of the glycosidic bonds in the sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…Tandem mass spectrometry (MS/MS) can be employed to generate glycosyl cations in complete isolation, and their gas-phase fragmentation has been extensively studied. 10 14 Recently, the use of MS in combination with infrared (IR) ion spectroscopy has emerged as a powerful method to determine the gas-phase structures of molecular ions in MS/MS 15 20 and to probe glycan structure. 21 26 …”
mentioning
confidence: 99%
“…Protonated carbohydrates present additional challenges, as they can undergo rearrangement reactions, most notably migration of fucose during collision-induced dissociation (CID) 6 . This migration process is still under investigation [7][8][9] , and a general structural understanding of the even simple protonated carbohydrate systems is only now starting to emerge 10 . For intact glycoconjugates (i.e.…”
Section: Introductionmentioning
confidence: 99%